2016
DOI: 10.1080/21623996.2016.1173804
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive IFNα/β signaling maintains expression of signaling intermediaries for efficient cytokine responses

Abstract: Interferons (IFNs) are a family of immunoregulatory cytokines with important roles in anti-viral and anti-tumor responses. Type I and II IFNs bind distinct receptors and are associated with different stages of the immune response. There is however, considerable crosstalk between these two cytokines with enhancement of IFNγ responses following IFNα/β priming and loss of IFNα/β receptor (IFNAR) resulting in diminished IFNγ responses. In this study, we sought to define the mechanism of crosstalk between the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…In this study, we have identified miR-203a-3p, which is induced upon RNA virus infection and poly(I:C) transfection. miR-203a-3p targets the 3'UTR of the IFNA pathway genes (IFNAR1, IFNA2, 4,7,10,14,16,17,21). We confirmed that miR-203a-3p forms a complex with Argonaut 2 (Ago2) protein, subsequently recruiting it to the transcripts of IFNA signaling pathway genes, including JAK1 and STAT1.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In this study, we have identified miR-203a-3p, which is induced upon RNA virus infection and poly(I:C) transfection. miR-203a-3p targets the 3'UTR of the IFNA pathway genes (IFNAR1, IFNA2, 4,7,10,14,16,17,21). We confirmed that miR-203a-3p forms a complex with Argonaut 2 (Ago2) protein, subsequently recruiting it to the transcripts of IFNA signaling pathway genes, including JAK1 and STAT1.…”
Section: Introductionsupporting
confidence: 52%
“…The type-I interferons (specially IFNα/β) are well characterized for the primary innate immune response and are necessary for defending against viruses (16)(17)(18). Type-I interferons are a family of cytokines dedicated to immunity against viruses, bacteria, parasites, and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…All type I interferons signal through a common receptor interferon alpha receptor (IFNAR). The IFNAR induces the Janus activated kinase-signal transducer and activation of transcription (JAK-STAT) pathway that control a large collection of genes through regulated expression of various signaling intermediaries (Guan et al, 2014;Messina et al, 2016;Olex et al, 2016).…”
Section: Role Of Human Interferons In Viral and Non-viral Liver Diseasementioning
confidence: 99%